2017
DOI: 10.1074/jbc.m117.783860
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of solute carrier family 13 member 5 disrupts energy homeostasis and inhibits proliferation of human hepatocarcinoma cells

Abstract: The solute carrier family 13 member 5 (SLC13A5), a sodiumcoupled citrate transporter, plays a key role in importing citrate from the circulation into liver cells. Recent evidence has revealed that SLC13A5 deletion protects mice from high-fat diet-induced hepatic steatosis and that mutation of the SLC13A5 orthologues in Drosophila melanogaster and Caenorhabditis elegans promotes longevity. However, despite the emerging importance of SLC13A5 in energy homeostasis, whether perturbation of SLC13A5 affects the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 48 publications
1
49
3
Order By: Relevance
“…1). Knocking down SLC13A5 in two human hepatoma cell lines caused a decrease in proliferation and cell cycle arrest at the G 1 phase, which were associated with decreased expression of two proteins involved in cell cycle control, p21 and cyclin B1 (5). Interestingly, similar effects were also observed when SLC13A5 was knocked down in an in vitro model of tumorigenicity (anchorage-dependent clonogenicity) and in an in vivo model, ectopic xenografts in mice, derived from human liver cancer cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Knocking down SLC13A5 in two human hepatoma cell lines caused a decrease in proliferation and cell cycle arrest at the G 1 phase, which were associated with decreased expression of two proteins involved in cell cycle control, p21 and cyclin B1 (5). Interestingly, similar effects were also observed when SLC13A5 was knocked down in an in vitro model of tumorigenicity (anchorage-dependent clonogenicity) and in an in vivo model, ectopic xenografts in mice, derived from human liver cancer cell lines.…”
mentioning
confidence: 99%
“…To examine the role of the citrate transporter SLC13A5 in liver cancer, Li et al (5) used knockdown of SLC13A5 in liver cancer cell lines to monitor the impact on modulating cell growth and oncogenic signaling (Fig. 1).…”
mentioning
confidence: 99%
“…(2,3) In contrast, Chen et al found that baseline levels of HBV DNA were not associated with HBV reactivation during the DAA-based therapies; however, this conclusion was based on only eight cases whose baseline level of HBV DNA varied from undetectable to high (1.1 3 10 6 IU/mL). Further analysis on the incidence of HBV reactivation among patients with different baseline levels of HBV DNA may yield alternative conclusions.…”
Section: To the Editormentioning
confidence: 74%
“…(1) We were well aware of the difference in the definition of hepatitis B virus (HBV) reactivation (HBVr) across the studies. However, due to the limited data reported in the included studies, we were unable to use a standardized definition, HBV replication 2 log increase from baseline levels, or a new appearance of HBV DNA to a level of 100 IU/mL (2) to adjust the pooled results. However, we have shown in the discussion that the pooled rate of HBVr (12.2%) could be higher in patients treated with DAAs if we standardize the definition.…”
Section: Replymentioning
confidence: 99%
“…The hypothesis was supported by a recent study that knocking down of mIndy inhibited human HCC cell proliferation by disrupting energy homeostasis in vitro. (5) Taken together, the oncogenic role of IL-6/STAT3 signing was not only mediated by its the well-known downstream antiapoptotic proteins and proliferationrelated cyclins, but factors that contributed to the remodeling of energy metabolism, such as mIndy, might be also needed to adapt the rapid cell proliferation in the development of HCC. In addition, although the contribution of mIndy in HCC cell growth was confirmed in vitro, whether Indy is required for HCC growth in vivo will be an interesting topic for further studies.…”
Section: To the Editormentioning
confidence: 99%